Health seeking behavior of men’s health disorders of among government servants in Kuantan: Prevalence study towards healthy ummah - Ahmad Arifin, Syamsul; Mat Yusof, Afzan; Md Isa, Muhammad Lokman (International Islamic University Malaysia, 2018)
As age advances most of body system will follow a process of deterioration too and the same goes for reproductive health. There is a gap between the prevalence of reproductive health disorders and rates of treatment. This gap among middle aged and older men is still wide compared to other chronic disease. In Islam, seeking medical treatment for the cure of diseases is part of the Prophet’s tradition and the Prophet (PBUH.) said in the Hadith the following: “For every disease there is a medicine, and if that medicine is applied to the disease, he will recover by Allah’s Leave.” Therefore the aim of this study is to identify a health seeking behaviour among men in for men’s health (MH) disorders in Kuantan. A cross sectional study was conducted among 157 respondents from four governments agencies and the data was collected using self-administered questionnaire modified from a valid and reliable measure. The results showed that 68.2% of the respondents (n=107) have high attitude in seeking for health regarding men’s health while for the rest of the respondents (n=50, 31.8%) have low attitude in seeking for MH. Men from the Service factor are perceived the highest compared the other two factors which are cultural and economic factors. This study showed that MH that includes reproductive disorders has always been taken lightly by the community itself. A Lack of awareness regarding ME issue causes men to ignore the importance of health screening. This should be improved in order to produce a healthy community for better Ummah since good heredity begins with good ME.